Former extremists: preventing and countering violence - Clubb, Gordon; Scrivens, Ryan; Islam, Md. Didarul (Causes and consequences of terrorism series, 2024)
This book is the first collection on former extremists in violence prevention work. It is particularly timely given formers' growing presence in violence prevention programs, especially in the context of countering and preventing violent extremism as well as peacebuilding. Although the engagement of formers in violence prevention has expanded in North and South America, throughout Europe, in the Middle East, and in Southeast Asia, their involvement has been controversial and contested. The objective of the book is to capture the variety of work formers are engaged in across a range of contexts, which can be broadly divided into three themes on their effectiveness, ethical considerations, and implementation. In addition to bringing together authors with different perspectives on the issue, the book assembles authors from a wide range of backgrounds and experiences, including academics, former extremists, peer mentors, program leaders, and practicing psychologists. As a result, the book not only captures ongoing policy debates but also contributes to the future direction of work of involving formers in violence prevention. "A considerable number of initiatives across the globe aiming to prevent violence have utilized or have been led by former extremists and former combatants (Formers). In the context of programs aiming to prevent and counter violent extremism (P/CVE), some former far-right extremists and former Islamist extremists have spoken in schools and have been enlisted as peer mentors to support extremists exit their respective movement. In the context of post-conflict initiatives, former members of armed groups have in some cases taken active roles to prevent violence at conflict flashpoints or have engaged youth to counter pro-paramilitary narratives"--